Therapeutic potential of hesperidin in Parkinson’s disease with dementia: inhibition of alpha synuclein and amyloid beta in Drosophila melanogaster (Nigerian Journal of Physiological Sciences, 2021)
Parkinson’s disease (PD) and dementia with Lewy bodies have several commonalities including neurochemical, morphological and clinical features as well as widespread of cortical and limbic α-synuclein and amyloid-β pathologies. Thus, we evaluated the action of hesperidin on α-synuclein and amyloid-β-induced neurodegeneration in Drosophila melanogaster. The disease causing human Aβ peptide or α- synuclein was expressed respectively, in Elav-GAL4 (pan-neuronally) and dopaminergic neurons (ddc-GAL4) using the UAS-GAL4 system. Flies were either grown on food media supplemented with or without hesperidin (HSD) (1, 5, or 10mM). Behavioral assays were carried to investigate the effect of treatment on fecundity, larval motility, climbing ability and lifespan. Aβ>Elav or α-syn>DDC caused significant decrease in fecundity, larva contraction, motility, survival rate, and climbing activities in flies indicative of neurodegeneration. However, supplementation of flies’ media with hesperidin (1mM, 5mM and 10mM) showed a dose-dependent increase in the number of line crosses in the egg laying, larva motility, climbing activity in comparison with flies grown on food media only. Conversely, supplementation of fly feed with HSD caused no significant change in lifespan. Findings from this experiment showed that hesperidin could be a potential neuroprotective agent in the amelioration of PD and AD pathogenesis